Understanding and Applying Guaranteed Maximum Price Contracts in Western Australia - Davis, Peter; Stevenson, D. (Australian Institute of Project Management, 2004)
The aim of this paper is to develop an understanding of Guaranteed Maximum Price and review awareness and its application to building procurement in Perth, Western Australia. The objectives were to determine the definition of Guaranteed Maximum Price (GMP), establish the relevance of GMP to the building industry in Perth and ascertain advantages and disadvantages of GMP. A qualitative research methodology was adopted where in depth semi structured qualitative interviews were carried out (n=10). Research questions asked if there was a generic understanding of GMP although there was a common principal that the price could not increase unless the client changed the scope. Further findings showed that GMP offered advantages over other methods of procurement that included price certainty for the client, a team approach to project delivery and faster completion. There was also significant disadvantages to contend with and these are described in the findings.